Pengaruh Media Interaktif Animasi Terhadap Hasil Belajar Siswa Mata Pelajaran IPA di Kelas V SD Swasta Ira Medan - Simamora, Sofia Ariani; Malinda, Leni; Hariati, Emy (Tematik: Jurnal Penelitian Pendidikan Dasar, 2024)
This study aims to examine the effectiveness of the Think-Pair-Share (TPS) cooperative learning model on the science learning outcomes of fourth-grade students at IRA Elementary School. The research question focused on whether the application of TPS could improve student performance compared to conventional teaching methods. The experimental research design involved 53 students, divided into two groups: one group applied the TPS model, and the control group used traditional teaching methods. The data collection included both test results (pretest and posttest) and non-test data, such as teacher observations and student participation. The findings revealed that the average score for students in the experimental group was 84.40, significantly higher than the 69.46 average in the control group. The statistical analysis showed that TPS positively impacted student learning outcomes. Based on these results, it is suggested that teachers adopt the Think-Pair-Share model to enhance science learning among elementary students.